2010
DOI: 10.1007/s10528-010-9366-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel SNPs of the Caprine Growth Hormone Secretagogue Receptor (GHSR) Gene and Their Association with Growth Traits in Goats

Abstract: Growth hormone secretagogue receptor (GHSR), a G protein-coupled receptor that binds ghrelin, plays an important role in the central regulation of pituitary growth hormone secretion, food intake, and energy homeostasis. This study analyzed polymorphism of the caprine GHSR gene as a genetic marker candidate for growth traits in goats. Two single nucleotide polymorphisms (GU014697:g.165G-->A and GU014697:g.548T-->C) were identified in exon 2 of the caprine GHSR gene by PCR-single-strand conformation polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…where, Y ijk is a record of individual phenotype value; U is the group average; marker k is a marker gene type effect; E ijk is a random error (Jin et al, 2010;Yuan et al, 2010;Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…where, Y ijk is a record of individual phenotype value; U is the group average; marker k is a marker gene type effect; E ijk is a random error (Jin et al, 2010;Yuan et al, 2010;Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In a study aimed at identifying genetic polymorphisms, which could serve as predictive markers of response to rhGH therapy, no such marker in GHSR was found [140]. In contrast, body length and weight of goats and pigs were significantly higher in animals carrying a GHSR polymorphism [141, 142].…”
Section: Genetic Conditions Associated With Normal Gh Sensitivitymentioning
confidence: 99%
“…In goats, association studies have revealed the existence of relationships between GH genotype and a wide array of growth parameters such as body length and height [63,64], and birth chest and weaning weight and height [65]. Similarly, the variability of the GH receptor has been associated with body length and height [65], while the growth hormone secretagogue receptor genotype displays significant associations with body length and body length index [66]. Myostatin (MSTN) belongs to the transforming growth factor-(TGF-) superfamily and it has been shown to repress muscular growth [67].…”
Section: Candidate Genes For Growth and Meat Quality Traitsmentioning
confidence: 99%